An application of Bacteriocin-Producing Vaginal Lactobacillus Crispatus IS30 in A Gel Formula Against Some Vaginal Pathogens - Tareq, Israa; Luti, Khalid Jaber Kadhum (Iraqi Journal of Science, 2022)
The aim of this study was to evaluate the possibility of using Lactobacillus cells as a probiotic to treat some vaginal infections. For this purpose, thirty Lactobacillus isolates were collected from vaginal samples subjected to a screening program to investigate their antagonism abilities against four vaginosis species: Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumonia and Proteus spp. Eighteen isolates were selected from the primary screening (agar plug diffusion method) based on their ability to inhibit the growth of 4 indicators which then subjected to a secondary screening program with two methods: detection of bacteriocin activity and biofilm forming capacity. The isolate Lactobacillus IS30 was selected based on its high bacteriocin production as well as being biofilm producer. Further identification tests revealed that isolate IS30 was Lactobacillus crispatus. Optimization experiments revealed that MRS broth was the best medium for bacteriocin and biomass production with glucose and yeast extract as best carbon and nitrogen sources. The maximum production observed in optimized culture was 15.9 mg/mL and 40 AU/mL for biomass and bacteriocin production respectively, hence this medium was used in the preparation of the formula containing Lactobacillus IS30 cells. Study the probiotic properties demonstrated the capability of Lactobacillus crispatus IS30 cells to tolerate the high acidity with an ability to adhere to vaginal epithelial cells. Moreover, Lactobacillus crispatus IS30 showed ability to auto-aggregation (72.66%) and 58% of Pseudomonas co-aggregation percentage after 5 hours. Lactobacillus crispatus IS30 cells was successfully incorporated into a gel bases formula and results revealed that cells have kept their viability over 14 days with an ability to produce and releasing the bacteriocin. The formula was tested against P. aeruginosa and E. coli and results confirmed its activity on both species.